Which Factors Affect the Occurrence of Off-Target Effects Caused by the Use of CRISPR/Cas: A Systematic Review in Plants - Modrzejewski, Dominik; Hartung, Frank; Lehnert, Heike; Sprink, Thorben; Kohl, Christian; Keilwagen, Jens; Wilhelm, Ralf (Frontiers in Plant Science, 2020)
CRISPR/Cas enables a targeted modification of DNA sequences. Despite their ease and efficient use, one limitation is the potential occurrence of associated off-target effects. This systematic review aims to answer the following research question: Which factors affect the occurrence of off-target effects caused by the use of CRISPR/Cas in plants? Literature published until March 2019 was considered for this review. Articles were screened for relevance based on pre-defined inclusion criteria. Relevant studies were subject to critical appraisal. All studies included in the systematic review were synthesized in a narrative report, but studies rated as high and medium/high validity were reported separately from studies rated as low and medium/low or unclear validity. In addition, we ran a binary logistic regression analysis to verify five factors that may affect the occurrence of off-target effects: 1. Number of mismatches 2. Position of mismatches 3. GC-content of the targeting sequence 4. Altered nuclease variants 5. Delivery methods. In total, 180 relevant articles were included in this review containing 468 studies therein. 79% of these studies were rated as having high or medium/high validity. Within these studies, 6416 potential off-target sequences were assessed for the occurrence of off-target effects. Results clearly indicate that an increased number of mismatches between the on-target and potential off-target sequence steeply decreases the likelihood of off-target effects. The observed rate of off-target effects decreased from 59% when there is one mismatch between the on-target and off-target sequences towards 0% when four or more mismatches exist. In addition, mismatch/es located within the first eight nucleotides proximal to the PAM significantly decreased the occurrence of off-target effects. There is no evidence that the GC-content significantly affects off-target effects. The database regarding the impact of the nuclease variant and the delivery method is very poor as the majority of studies applied the standard nuclease SpCas9 and the CRISPR/Cas system was stably delivered in the genome. Hence, a general significant impact of these two factors on the occurrence of off-target effects cannot be proved. This identified evidence gap needs to be filled by systematic studies exploring these individual factors in sufficient numbers.